Does increased aromatase activity in adipose fibroblasts cause low sexual desire in patients with HIV lipodystrophy?. (1st February 2002) - Goldmeier, D; Scullard, G; Kapembwa, M; Lamba, H; Frize, G
Abstract : There is evidence from our own unit and other workers that many patients who have lipodystrophy on HAART given for HIV disease also have raised oestrogen levels and complain of low sexual desire. This hypothesis paper discusses a possible pathological mechanism for these changes—an increase in the number of fibroblasts and macrophages present in lipoatrophic areas that could convert testosterone to oestrogen by intracellular aromatisation. This process is known to be enhanced by increased levels of tumour necrosis factor, interleukin 6 (IL-6), and hydroxycorticosteroids present in many patients with HIV lipodystrophy. Treatment options are discussed, including aromatase inhibitors and testosterone.